Selective Cross‐Ketonization of Carboxylic Acids Enabled by Metallaphotoredox Catalysis. Issue 52 (28th November 2022) - Whyte, Andrew; Yoon, Tehshik P.
Abstract: Carboxylic acids are attractive building blocks for synthetic chemistry because they are chemically stable, abundant, and commercially available with substantial structural diversity. The process of combining two carboxylic acids to furnish a ketone is termed ketonization. This is a potentially valuable transformation that has been underutilized in organic synthesis due to the harsh reaction conditions generally required and the lack of selectivity obtained when coupling two distinct carboxylic acids. We report herein a metallaphotoredox strategy that selectively generates unsymmetrical ketones via cross‐ketonization of two structurally dissimilar carboxylic acids. Cross‐selectivity is achieved by exploiting divergent reactivity of differentially substituted acids towards critical one‐ and two‐electron processes in the proposed coupling mechanism. This method is broadly applicable to a variety of functionalized carboxylic acids. It can also be applied to acids of similar steric profile by exploiting differences in their relative rates of decarboxylation. Abstract : Unsymmetrical ketones can be prepared through selective coupling of two structurally distinct carboxylic acids without the need for preactivation of either partner. This photoredox cross‐ketonization strategy exploits differences in the rates of key one‐ and two‐electron activation steps using the two reactants.